New records of warm-temperate water fishes in central Patagonian coastal waters (Southwestern South Atlantic Ocean) - Bovcon, Nelson Darío; Cochia, P. D.; Gongora, M. E.; Gosztonyi, Atila Esteban (Journal of Applied Ichthyology)
In the Province of Chubut (43°S-47°S), from 2001 to 2005 an on-board observers program analyzed 18903 fishing hauls captured at depths of 19-104m. Sport fishing tournaments near Puerto Rawson, Chubut, were also monitored from 2004 to 2006. The aim was to document the southward expansion of five cartilaginous fish species and ten bony fish species caught in Central Patagonian waters (Argentina): Psammobatis extenta, Psammobatis bergi, Atlantoraja castelnaui, Sympterygia acuta, Torpedo puelcha, Selene setapinnis, Oncopterus darwini, Dules auriga, Mullus argentinae, Cynoscion guatucupa, Prionotus nudigula, Conger orbignyanus, Urophycis brasiliensis, Trachurus lathami, and Trichiurus lepturus. Reproductive populations of S. acuta, O. darwini and C. guatucupa were detected in the Engaño Bay area close to Puerto Rawson (43°10'S-43°19'S). The newly reported fishes pertain to warm-temperate waters, where most of the species are native to the Argentinean Zoogeographic Province. One likely hypothesis explaining their occurrence in the area is the prevalence of higher water temperatures in recent times in the San Jorge Gulf and adjacent waters. Another likely hypothesis is the increase in sampling and catch efforts in Patagonian coastal areas and also improved capabilities in taxonomic recognition of the species. Fil: Bovcon, Nelson Darío. Universidad Nacional de la Patagonia "San Juan Bosco"; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Cochia, P. D. Universidad Nacional de la Patagonia "San Juan Bosco"; Argentina Fil: Gongora, M. E. Universidad Nacional de la Patagonia "San Juan Bosco"; Argentina Fil: Gosztonyi, Atila Esteban. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina